The Role of The Nation and Political Union (Kesbangpol) DKI Jakarta in Doing Community Organization Development - Sabena Sabena; Syerli Hayati; Taufan Bakri (Universitas Mercu Buana, 2022)
The number of community organizations that have sprung up in the DKI Jakarta area and its surroundings continues to grow and requires serious attention from the government and the public, considering that the existence of these organizations is feared to be incompatible with its true function, as a link to convey input to the government, related parties from the voice of the community. Ormas as the front line in knowing the problems around them, the role of mass organizations in a picture of life that occurs in society, if left alone without supervision and guidance is not impossible for mass organizations to become a tool of political propaganda and become a weapon to create conflict in society, because this For this reason, it is necessary to provide guidance to all community organizations so that they return to their functions as government control, the chain of messengers, information on phenomena that occur in the midst of society, providing input from all elements of society. In this case, the national and political unitary body plays a role in providing guidance to mass organizations, starting from the establishment permit letter, determining the activity permit decision letter and knowing who is the administrator. Monitoring activities continue to be carried out by synergizing programs that can directly involve the mass organizations. Part of the coaching is expected to be able to control the mass organizations so that they do not become wild and misfunction.